Multilevel analysis of coach leadership, group cohesion and collective efficacy in semiprofessional football teams - Leo, F. M.; González-Ponce, I.; Pulido, J. J.; López-Gajardo, M. A.; García-Calvo, T. (International Journal of Sport Psychology, 2022)
This study examined how perceptions of leadership behavior in semi-professional sport predicted group cohesion and collective efficacy in a sample of Spanish football players. We adopted a longitudinal perspective, taking measures at the beginning, the middle, and the end of a sport season, and three levels of analyses were specified: intra-individual, inter-individual, and inter-team level. Multilevel modeling analysis showed that perceptions of positive leadership behaviors, such as training instruction, social support, positive feedback, and democratic behaviors, were a stronger predictor of a high level of cohesion and collective efficacy than were perceptions of coaches` autocratic behavior. Predictive effects differed as a function of time, level of analyses and the outcome variable under investigation. The results indicate the importance of considering the coaches` leadership styles when examining group cohesion and collective efficacy at different levels of analyses in semi-professional sports